2010
DOI: 10.1310/tsr1702-79
|View full text |Cite
|
Sign up to set email alerts
|

Do People With Aphasia Want Written Stroke and Aphasia Information? A Verbal Survey Exploring Preferences for When and How to Provide Stroke and Aphasia Information

Abstract: A phasia can be defined as "the loss or impairment of language function." 1(p49) It is a multimodality disorder that manifests in difficulties with speaking, reading, and writing.1 Various studies have investigated the prevalence of aphasia resulting from stroke, estimating between 10% to 18% of stroke survivors will have aphasia long term.2-4 Given the language diffi culties encountered by people with aphasia, there is a growing recognition of the need to produce aphasia-friendly written health information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Information sheets and consent forms were designed using "aphasia friendly" principles to maximise comprehension (Rose, Worrall, Hickson, & Hoffmann, 2010). Translations of written materials were prepared for non-English speaking participants.…”
Section: Informed Consentmentioning
confidence: 99%
“…Information sheets and consent forms were designed using "aphasia friendly" principles to maximise comprehension (Rose, Worrall, Hickson, & Hoffmann, 2010). Translations of written materials were prepared for non-English speaking participants.…”
Section: Informed Consentmentioning
confidence: 99%
“…15 The majority of stroke patients and their carers would like to receive written information, 16,17 although dissatisfaction with the quality of the written materials provided has been identifi ed as a barrier to adequate stroke education by patients, 18 carers, 18 and stroke health professionals. 19 Despite the reading diffi culties that are often experienced by patients with aphasia, Rose et al 20 examined the information preferences of 40 patients with aphasia and found that most wished to receive written materials. For all patients, written health education materials can only be of benefi t if they can be understood by the recipient.…”
mentioning
confidence: 99%
“…What more patients with aphasia still experience various problems, e.g. mobile phone use can be problematic [40], some of them still need printed education materials in formats preferred by patients with aphasia [41,42,43].…”
Section: Much Easier Example: Aphasiamentioning
confidence: 99%